2021
DOI: 10.3389/fimmu.2021.697622
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Immunological Parameter Landscape in Coronavirus Disease 2019 Patients With Different Outcomes

Abstract: ObjectivesThe longitudinal and systematic evaluation of immunity in coronavirus disease 2019 (COVID-19) patients is rarely reported.MethodsParameters involved in innate, adaptive, and humoral immunity were continuously monitored in COVID-19 patients from onset of illness until 45 days after symptom onset.ResultsThis study enrolled 27 mild, 47 severe, and 46 deceased COVID-19 patients. Generally, deceased patients demonstrated a gradual increase of neutrophils and IL-6 but a decrease of lymphocytes and platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…However, it would be the early immunological features which define the prognosis of the disease in these patients. Notably, proinflammatory monocytes were found to be elevated in the circulation at early stages of the disease in deceased patients [75] together with delayed antibody response which correlated with poor clinical outcome of the disease [82]. This late onset in the humoral response is in line with the delay in differentiation of plasma cells in severe [83].…”
Section: The Uglymentioning
confidence: 85%
See 1 more Smart Citation
“…However, it would be the early immunological features which define the prognosis of the disease in these patients. Notably, proinflammatory monocytes were found to be elevated in the circulation at early stages of the disease in deceased patients [75] together with delayed antibody response which correlated with poor clinical outcome of the disease [82]. This late onset in the humoral response is in line with the delay in differentiation of plasma cells in severe [83].…”
Section: The Uglymentioning
confidence: 85%
“…Interestingly, although not all COVID-19 patients develop severe respiratory illness [73], some cases would progress to a cytokine storm, acute respiratory distress syn-drome (ARDS), and multiorgan dysfunction [74]. As a matter of act in fatal cases, inflammatory increased cytokines [75] together with mononuclear infiltrate in the lungs have been observed throughout the time [76]. Moreover, inflammatory CD14+/CD16+ monocytes, which are related to chronic inflammation and autoimmunity [77][78][79], have been found to be expanded in the peripheral blood of those patients who require hospitalization [80,81] reinforcing the idea that innate immune cells determine the outcome of cytokine dysregulation.…”
Section: The Uglymentioning
confidence: 99%
“… No change in e-MDSC (proportion) No [ 2 ] 14 N = 58 (COVID-19: 13 moderate, 37 severe; HD: 8) PB No Fresh M-MDSC: HLA-DR -/dim CD11b + CD14 + CD15 − PMN-MDSC: HLA-DR -/dim CD11b + CD14 − CD15 + Increase in M-MDSC and PMN-MDSC (proportion, in patients as compared to HD) No [ 84 ] 15 N = 26 (COVID-19: 13 convalescent; HD: 13) PB Yes Fresh M-MDSC: Lin − HLA-DR -/dim CD11b + CD14 + CD15 − PMN-MDSC: Lin − HLA-DR -/dim CD11b + CD14 − CD15 + e-MDSC: Lin − HLA-DR − CD11b + CD14 − CD15 − Increase in PMN-MDSC (proportion, in convalescent patients as compared to HD). No change in M-MDSC and e-MDSC (proportion) Inhibition of antigen-nonspecific T cell proliferation [ 68 ] 16 N = 67 (COVID-19: 26 mild, 15 severe; HD: 26) PB Yes Fresh M-MDSC: HLA-DR − CD11b + CD66b − CD14 + CD15 − PMN-MDSC: HLA-DR − CD11b + CD66b + CD14 − CD15 + Increase in M-MDSC and PMN-MDSC (proportion, in patients as compared to HD; increase in PMN-MDSC in mild patients as compared to severe patients) No [ 70 ] 17 N = 120 (COVID-19: 27 mild, 47 severe, 46 deceased) PB No Fresh M-MDSC: HLA-DR − CD14 + Increase in M-MDSC (proportion, in deceased patients as compared to mild and severe patients) No [ 3 ] 18 N = 80 (COVID-19: 40 ICU discharged, 40 ICU deceased) PB No Fresh <...>…”
Section: Mdscs In Covid-19mentioning
confidence: 99%
“…Falck-Jones et al demonstrated that an early increase in M-MDSC frequency was associated with later disease severity [ 63 ]. A study by Tang et al , which enrolled 27 mild, 47 severe and 46 deceased COVID-19 patients, demonstrated that an M-MDSC cutoff value of ≥10%, as estimated in the CD14 + gate, predicted COVID-19 mortality [ 3 ]. On the other hand, a study by Mortaz et al of 37 severe and 13 moderate COVID-19 patients showed that neither the frequency of M-MDSC nor PMN-MDSCs in peripheral blood predicted either the survival of patients or severity of infection [ 84 ].…”
Section: Mdscs In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation